Facile, non-destructive characterization of 2d photonic crystals using UV-vis-spectroscopy12. Issue 6 (25th January 2018) - Schöps, V.; Lenyk, B.; Huhn, T.; Boneberg, J.; Scheer, E.; Offenhäusser, A.; Mayer, D.
Abstract : The quality of particle monolayers and size evolution of their particles during dry etching can be monitored by radiative losses of photonic modes into dielectric substrates. Abstract : We present a simple and non-destructive method for characterizing and quantifying the quality of two-dimensional (2D) close-packed arrays of submicron dielectric spheres. Utilizing radiative losses of photonic modes created by the 2D crystals into dielectric substrates we are able to monitor the quality of the particle monolayer during assembly and the size evolution of the individual particles during dry etching. Using an advanced interfacial assembly technique we prepare particle monolayers on glass and characterize the spectral behaviour of the radiative loss regarding different lattice constants, dielectric substrates and layer qualities. The effect of diameter reduction during dry etching is analysed and a simple model is proposed, which enables non-destructive, on spot characterization of the particle layer with sub-20 nm resolution using UV-vis spectroscopy.